PEMANFAATAN TUMBUHAN SECARA TRADISIONAL DI TAMAN NASIONAL GUNUNG HALIMUN - Syamsul Hidayat; Izu Andry Fijridiyanto (BERITA BIOLOGI, 2002)
Gunung Halimun National Park (GHNP) is one of the remaining tropical forest in Java, still has high interaction with people who live in the surrounding areas.Eventhough there were some studies on ecology and ethnobotany in this area,it is still lacking of information on these subjects.This paper presented the results of ethno-ecology studies at several areas in GHNP such as East Halimun sector (around Gn.kendeng) and South Halimun sector (around Pangguyangan). The studies were carried out through vegetation analysis with Random Quadrats method and Participation method with interview technique.By these methods data were collected for the Important Value Index (IVI) and the Use Value Index (UVI) of species.These values showed that rasamala (Altingia excelsa), for tree stage, has the highest IVI and UVI but for the sapling stage the IVI is low. Kianak (Castanopsis acuminatissima) for tree and sapling stages the IVI is high but the UVI is low, while for maja (Magnolia macklottii), the UVI is high but the IVI is low for both tree and sapling stages. Based on these data, analyzed was done regarding the presence and the prospect of these species, in the context of the lifestyle of the villagers.